The Structural Funds and the Cohesion Fund as an external sources of funding local government units - Gęsina, Milena (Management and Administration Journal, 2024)
Possession of financial resources is a key condition for the proper functioning of thelocal government and has a significant impact on the development. With the increasing numberof tasks that local authorities must carry out, growing demand for cash. Necessary in the localgovernment unit is to have income of their own, which are supported by external sources.